2015
DOI: 10.2174/1570159x13666150115220221
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Akathisia in the Treatment of Schizophrenia with Aripiprazole, Asenapine and Lurasidone: A Meta-Analysis

Abstract: Akathisia is a troubling side effect that leads to non-adherence with antipsychotic regimens. Second generation antipsychotics (SGAs) tend to cause less akathisia than older agents but the risk still exists and rates vary between agents. Little is known about the incidence of akathisia among the newer SGAs. The purpose of this study was to conduct a meta-analysis of akathisia incidence rates for three of the newer SGAs: aripiprazole, asenapine, and lurasidone. Data were drawn from published and unpublished cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 43 publications
7
22
0
3
Order By: Relevance
“…Since N-dealkyl-aripiprazole and hydroxy-aripiprazole are inactive metabolites, the inactivation pathways may become the principal route of aripiprazole metabolism upon co-medication with metoprolol or propranolol, resulting in potential modification of aripiprazole efficacy. Aripirazole has been reported to have a significantly higher risk of akathisia compared to other second generation antipsychotics [58], and beta-adrenerg receptor blockers, such as propranolol or metoprolol, are frequently used in the clinical management of antipsychotics induced akathisia [59]. The fact that co-administration of aripiprazole and beta-blockers is common, underlines the clinical significance of our findings.…”
Section: Discussionsupporting
confidence: 60%
“…Since N-dealkyl-aripiprazole and hydroxy-aripiprazole are inactive metabolites, the inactivation pathways may become the principal route of aripiprazole metabolism upon co-medication with metoprolol or propranolol, resulting in potential modification of aripiprazole efficacy. Aripirazole has been reported to have a significantly higher risk of akathisia compared to other second generation antipsychotics [58], and beta-adrenerg receptor blockers, such as propranolol or metoprolol, are frequently used in the clinical management of antipsychotics induced akathisia [59]. The fact that co-administration of aripiprazole and beta-blockers is common, underlines the clinical significance of our findings.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, it was important to examine the potential influence of psychotic severity, owing to a previously reported relationship by which the severity of psychotic episode predicted more anxiety [26] and concerns about symptom differentiation that prompted a call to account for psychotic severity in anxiety studies in this population [27]. Our and other studies, furthermore, confirmed the presence of anxiety symptoms during the acute phase among some patients, toppling the outdated notion that anxiety symptoms in schizophrenia would be limited to the post-psychotic period [18,31,45].…”
Section: Discussionsupporting
confidence: 68%
“…Undifferentiated anxiety was found discernible without evidence of a confounding influence by akathisia, the severity of psychotic symptoms, or medication. It was important to examine akathisia as potential confounder as it may be confused with anxiety and vice versa [3,28,45,46]. Similarly, it was important to examine the potential influence of psychotic severity, owing to a previously reported relationship by which the severity of psychotic episode predicted more anxiety [26] and concerns about symptom differentiation that prompted a call to account for psychotic severity in anxiety studies in this population [27].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2015 revealed that risk of akathisia was higher for Aripiprazole, Asenapine and Lurasidone. 23 Chronic insomnia is a problem in Schizophrenics and two cases of insomnia was reported at a dose of 5mg/day. The addition of benzodiazepine resolved this problem.…”
Section: Resultsmentioning
confidence: 99%